Identification of Upwelling Area of the Western Territorial Waters of Indonesia From 2000 To 2017 - Eko Supriyadi; Rahmat Hidayat (Indonesian Journal of Geography, 2020)
The Western Waters of Indonesian (WWI) present a diverse interaction of ocean-atmosphere dynamics. One of them represents the event of Indian Ocean Dipole (IOD), El Niño–Southern Oscillation (ENSO), and upwelling. The objective of this study is to determine the dynamics of chlorophyll-a concentration (Chl–a), especially during IOD and ENSO. Also, this study is aimed to examine the temporal and spatial distribution of the upwelling area from 2000 to 2017. The data utilized consisted of Chl–a, wind stress, Sea Level Anomaly (SLA), and Sea Surface Temperature (SST). The technique used to determine the upwelling area was by examining the maximum conditions of Chl–a, the low temperature of SST, and SLA. The results showed the sea surface temperature had a relationship with the concentration of Chl–a. It was obtained if the Directional Movement Index (DMI) and N3.4 (Niño 3.4 Index) moved stably (not too fluctuation) resulting in high concentrations of Chl–a. High standard deviations of SST are recognized around the Sunda Strait (June – October). When the standard deviation of SST is high, there is also a tendency for high Chl–a concentrations, while the results of empirical calculations show that large areas of upwelling occurred in January and September respectively at 12,447.72 km2 and 8,146.20 km2. Based on the results of the analysis, it can be concluded that the upwelling does not only occur at the coastal area of Western Sumatra (coastal upwelling), but it also occurs in the eastern territorial waters of the Indian Ocean. In addition, the upwelling area has the same pattern as the Chl–a concentration in January - October.